(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Due to the onset of the last economic crisis, the recent focus of policy makers has been shifted from economic development to the possibility of fast identification of the sources of financial shocks and imbalances in order to quickly solve the extreme stresses that can emerge in the financial system. Therefore, the interdependences of financial institutions and financial leverages as well as the causes of endogenous changes of real interest rates and the differences emerging between interest rates and the rates affecting expenditure are observed more often in this context. The paper emphasizes this problem as well as the problem of the need for a different structure of the financial system and its participants that would contribute to a higher level of economic development. In this context, on the example of data on the Croatian capital market shareholders’ structure and data on the amount of loans to companies in the period from 2006 to 2018, a model was developed via ANFIS. The model indicated the positive and negative impacts of banks and shareholders’ structure on the capital market.